2014
DOI: 10.4314/sajas.v43i5.6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary conjugated linoleic acid (CLA) on the metabolism and reproduction of dairy cows

Abstract: Rumen-protected conjugated linoleic acid (CLA) reportedly improves fertility in lactating dairy cows by reducing the postpartum interval to first ovulation and enhancing the circulating insulin-like growth factor-I (IGF-I) levels. The objectives of this study were to evaluate the blood metabolites, hormones, follicular fluid (FF) and liver for the effect of CLA supplementation (50 g top-dressed daily from 15 days pre-partum to 65 days in milk -DIM -). Pre-partum Holstein cows (n = 24) were assigned to two trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Literature data in terms of the effect of CLA on DMI of cows are inconsistent. Some authors described an increased DMI (Esposito et al., ), but on the other hand, numerous studies suggested that CLA is not influencing feed intake significantly (Overton et al., ; Bernal‐Santos et al., ), or indeed, it has a negative effect on it (Moallem et al., ; Pappritz et al., ). Whether the higher pen DMI was an effect of CLA cannot be unequivocally concluded from our results.…”
Section: Discussionmentioning
confidence: 99%
“…Literature data in terms of the effect of CLA on DMI of cows are inconsistent. Some authors described an increased DMI (Esposito et al., ), but on the other hand, numerous studies suggested that CLA is not influencing feed intake significantly (Overton et al., ; Bernal‐Santos et al., ), or indeed, it has a negative effect on it (Moallem et al., ; Pappritz et al., ). Whether the higher pen DMI was an effect of CLA cannot be unequivocally concluded from our results.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation of conjugated linoleic acid (CLA) in the early postpartum period is a possible strategy to decrease negative energy balance and improve postpartum metabolic health by reducing milk fat secretion [ 5 7 ]. This scenario is undesirable by many dairy producers who sell milk in component compensated markets.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding these isomers in a rumen-protected form to transition dairy cows reduces negative energy balance and NEFA and BHB levels in blood (Mattos et al, 2000;Castaneda-Gutierrez et al, 2007;Trevisi and Bertoni, 2008;Esposito et al, 2013). CLA supplementation increases DMI and some of the negative acute phase proteins such as albumin and cholesterol Esposito et al, 2013). Moreover, in vitro studies showed that CLA have a beneficial role in protecting PON1 from oxidative inactivation, as well as in its stabilization in a concentration-dependent action against various oxidative inactivation systems (Su et al, 2003;Nguyen and Sok, 2004).…”
Section: Fat Supplementation In Transition Dietmentioning
confidence: 99%
“…Lately, researchers have been focusing mainly on the isomers cis-9, trans-11 and the trans-10, cis-12. Feeding these isomers in a rumen-protected form to transition dairy cows reduces negative energy balance and NEFA and BHB levels in blood (Mattos et al, 2000;Castaneda-Gutierrez et al, 2007;Trevisi and Bertoni, 2008;Esposito et al, 2013). CLA supplementation increases DMI and some of the negative acute phase proteins such as albumin and cholesterol Esposito et al, 2013).…”
Section: Fat Supplementation In Transition Dietmentioning
confidence: 99%